Loss and Substitution: The Ecology of Production in Southwestern Saskatchewan, 1860-1930 - Potyondi, Barry (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1994)
AbstractThe history of ecological change in southwestern Saskatchewan, and arguably on the Canadian plains as a whole, has been marked by the loss of indigenous species and their replacement with a smaller number of domestic species valued chiefly for the commercial profits they generate. This decline in natural biodiversity accelerated as regional residents embraced distinct manifestations of market capitalism between 1860 and 1930. Through participation in the robe trade, natives and Métis contributed significantly to the loss of the traditional "buffalo landscape" of the plains before 1880. After 1880, ranchers introduced the grazing patterns of domestic cattle and horses, decimated the population of natural predators, exceeded the grazing capacity of the range, and ultimately affected its vegetational composition. Wheat farmers, who had obliged ranchers to make many of these drastic changes, altered the environment to an unprecedented degree through their abiding devotion to monoculture production. The cumulative result was profound alteration of the nineteenth-century plains ecosystem with attendant economic and social disruption.